2021
DOI: 10.3389/fnins.2021.697299
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Resting-State Spontaneous Brain Activity in Patients With Allergic Rhinitis: A Pilot Neuroimaging Study

Abstract: BackgroundAllergic rhinitis (AR) is an inflammatory disorder of the nose caused by immunoglobulin E (IgE)-mediated immune response to allergens. Apart from the typical symptoms of sneezing, itching, rhinorrhea, and nasal congestion, behavioral complications were also reported to be associated with the progression of AR, such as cognitive deficits, mood changes, memory decline, attention deficiency, poor school performance, anxiety, and depression. Recent human studies have suggested that alterations in brain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
(86 reference statements)
0
6
0
1
Order By: Relevance
“…Whether this is a secondary phenomenon or a causal relationship is unclear. Much studied serological parameters were inconclusive, however, in a pilot study with a small collective, Gao et al [125] demonstrated for the first time altered brain activities in resting functional neuroimaging for patients with allergic rhinitis compared to a control group. Fuhrmann et al [126], using an AOK cohort for Germany with 41,484 children, showed that children who received antihistamines in the first two years of life (N = 5540) but did not show atopic dermatitis had a 35 % increased risk of developing ADHD.…”
Section: Comorbidities and New Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether this is a secondary phenomenon or a causal relationship is unclear. Much studied serological parameters were inconclusive, however, in a pilot study with a small collective, Gao et al [125] demonstrated for the first time altered brain activities in resting functional neuroimaging for patients with allergic rhinitis compared to a control group. Fuhrmann et al [126], using an AOK cohort for Germany with 41,484 children, showed that children who received antihistamines in the first two years of life (N = 5540) but did not show atopic dermatitis had a 35 % increased risk of developing ADHD.…”
Section: Comorbidities and New Therapeutic Approachesmentioning
confidence: 99%
“…Ob dies ein sekundäres Phänomen ist oder ein kausaler Zusammenhang besteht ist unklar. Vielfach untersuchte serologische Parameter waren uneindeutig, allerdings konnte Gao et al [125] in einer Pilotstudie an einem kleinen Kollektiv erstmalig im funktionellen Neuroimaging in Ruhe veränderte Hirnaktivitäten für Patienten mit allergischer Rhinitis im Vergleich zu einer Kontrollgruppe nachweisen. Fuhrmann et al [126] zeigen anhand einer AOK-Kohorte für Deutschland mit 41.484 Kindern, dass Kinder, die in den ersten zwei Lebensjahren Antihistaminika erhielten (N = 5540), aber keine atopische Dermatitis zeigten, ein um 35 % erhöhtes Risiko für die Entwicklung eines ADHS hatten.…”
Section: Komorbiditäten Und Neue Therapieansätzeunclassified
“…Notably, most of the above findings were based on animal models, as there are ethical regulations governing the conduct of research involving human subjects with AR-related depression, especially when invasive manipulations are involved. Fortunately, as a non-invasive examination tool, functional magnetic resonance imaging (fMRI) has been applied to study the brain response in AR patients ( 32 , 33 ), which provides the possibility to further directly study brain alterations in depressed AR patients. In recent years, China maintains a leading position in animal studies on the mechanisms of depression in AR.…”
Section: Causes and Mechanisms Of Depression In Armentioning
confidence: 99%
“…Based on studies between AR and brain‐related symptoms, the mechanisms by which AR leads to brain response may be as follows and illustrated in Figure 1 (Gao et al, 2021): (1) Inflammatory mediators produced during AR inflammation penetrate the blood–brain barrier and lead to the emergence of dominant neurological symptoms by activating different brain regions. But the pathways through which its inflammatory factors enter the brain from the external environment are not fully elucidated in AR research.…”
Section: Summary and Prospectmentioning
confidence: 99%
“…In conclusion, the pathogenesis of AR neurological symptoms is quite complex involving abnormal neuro‐immunity inflammation and EEG activity, which could disturb the various physiological processes in different brain regions and neural circuits to induce different brain symptoms, as summarized in Table 1. Through the above overview of AR‐induced brain response, we can use interference with relevant targets in the “nose‐brain communication” loop as a treatment to improve AR‐induced brain function‐related symptoms and improve the quality of life of patients (Gao et al, 2021). Although there have been many studies on the mechanism of “nose‐brain communication” in AR, most of them have only revealed its relevance, and most studies are based on animal models and cell cultures, which have certain limitations.…”
Section: Summary and Prospectmentioning
confidence: 99%